Variability and predictability of performance times of elite alpine skiers - Spencer, M.; Reid, R.; Gilgien, M.; Hopkins, W. G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The variability in performance of elite athletes between competitions provides useful information for research on factors affecting medal-winning performance. The aim of this study was to estimate the variability of performance of alpine skiers in international competitions. Methods: Official race times and course information for men`s and women`s downhill, super G, giant slalom and slalom in World Cup competitions from seasons 2001-2013 were downloaded from fis-ski.com. In analyses of the top 30 athletes from each race there were 93-113 athletes competing in up to 26-64 races at 12-31 venues. In analyses restricted to the annual top-10 athletes there were 40-55 athletes in up to 41-73 races. A linear mixed model of log-transformed race times for each event provided estimates of within-athlete race-to-race variability (expressed as a coefficient of variation, CV) after adjustment for differences in mean race time arising from race terrain and snow conditions. Predictability of performance was expressed as an intraclass correlation representing the mean correlation between pairs of races within seasons. Results: Within-athlete race-to-race variability in performance time was similar for men and women in the various events for top-30 athletes (CV of 0.54-0.73%) and for annual top-10 athletes (0.57-0.76%). Predictability of performance for men and women for top-30 athletes was low to moderate (correlations of 0.18-0.27 and 0.28-0.43, respectively), and poor to low for top-10 athletes (0.04-0.10 and 0.11-0.30). Discussion: The race-to-race variability of the best alpine skiers is similar to that of elite skeleton athletes, another sport where speed is determined partly by gravity (Bullock et al., 2009). The variability is approximately half that of endurance sports such as cross-country skiing (Spencer et al., 2014). Estimates of the smallest worthwhile performance enhancement (0.3x within-athlete variability) will assist researchers investigating factors affecting performance of elite skiers.